2021
DOI: 10.1097/pq9.0000000000000440
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Initiative to Improve Discharge Timeliness and Documentation

Abstract: Introduction: Discharge communication is critical for the continuity of patient care. However, discharge summaries are often not available in time for follow-up visits, and the content is inconsistent. We aimed to decrease the average time to discharge summary completion by 25%, reduce deficiencies (information errors) by 50%, and increase discharge summary template use to >80% in 6 months. Methods: A pediatric interprofessional team used quality improvement methods to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Improvement strategies could include: setting clear expectations for when discharge summaries must be completed, discharge summary template redesign to automate inclusion of the discharge prescription list and OMP, and protected time for medical staff to complete discharge summaries. 14,15 Initial OMP implementation in orthopaedic units informed improvements to implementation for other surgical units. Whilst poor medical staff engagement with passive hospital education activities may have been heightened following COVID-19 pandemic pressures, these approaches have also had limited effectiveness at other times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvement strategies could include: setting clear expectations for when discharge summaries must be completed, discharge summary template redesign to automate inclusion of the discharge prescription list and OMP, and protected time for medical staff to complete discharge summaries. 14,15 Initial OMP implementation in orthopaedic units informed improvements to implementation for other surgical units. Whilst poor medical staff engagement with passive hospital education activities may have been heightened following COVID-19 pandemic pressures, these approaches have also had limited effectiveness at other times.…”
Section: Discussionmentioning
confidence: 99%
“…Our hospital is currently reviewing our discharge summary template and workflow to improve the timeliness and quality of discharge documentation for GPs. Improvement strategies could include: setting clear expectations for when discharge summaries must be completed, discharge summary template redesign to automate inclusion of the discharge prescription list and OMP, and protected time for medical staff to complete discharge summaries 14,15 …”
Section: Discussionmentioning
confidence: 99%
“…Notably, we did not see a reduction in character count in discharge summaries even as the usage of laboratory Smar-tLinks was reduced by half. This is likely due to a concomitant change in our Discharge Summary template that added a "Suggested Next Steps for Primary Care Provider" section, 14 which highlighted significant follow-up needs and would be considered relevant note information rather than note bloat.…”
Section: Discussionmentioning
confidence: 99%
“…For uniqueness, studies assessed if records were unexpectedly duplicated, for example in primary keys [78] or patient names [94]. Likewise, timeliness was consistently assessed as the difference in time between point of data capture versus actual timing of events [73,74,76,80,81,103]. In contrast, some of the DQ concepts reported could not be classified according to the DAMA DQ framework, including simplicity, acceptability, flexibility, stability, usefulness [76], and conformance to a specified data model [89].…”
Section: Data Quality Assessment Methodsmentioning
confidence: 99%
“…Twenty studies reported using quantitative or qualitative data analysis before planning an intervention. Qualitative analysis involved assessment of clinical workflow inefficiencies through process mapping techniques or staff surveys [73,107]. In contrast, quantitative analysis involved an assessment of DQ with interpretations of possible root causes [94,95].…”
Section: Interventions For Improvementmentioning
confidence: 99%